Sodium Glucose Cotransporter-2 Inhibitor Protects Against Diabetic Neuropathy and Nephropathy in Modestly Controlled Type 2 Diabetes: Follow-Up Study - Ishibashi, Fukashi; Kosaka, Aiko; Tavakoli, Mitra (Frontiers in Endocrinology, 2022)
Aims: This three-year follow-up study aimed to elucidate whether sodium-glucose cotransporter-2 inhibitors (SGLT2is) have any protection against diabetic microvascular complications in patients with type 2 diabetes via reducing variability in glycemia and extraglycemic factors or their averages. Methods: Two type 2 diabetic cohorts of 40 and 73 patients treated with or without SGLT2i along with 60 control subjects were recruited. Two diabetic cohorts matched for HbA1c levels and oral hypoglycemic agents other than SGLT2is underwent glycemic control with or without SGLT2is more than two years. The urinary albumin to creatinine ratio (ACR), estimated glomerular filtration rate (eGFR) every 3 months and fundus photography, neuropathy outcome measures and mean Z-score of 8 neurophysiological tests were determined at baseline and endpoint. Glycemic variability, evaluated by the coefficient of variation of monthly measured HbA1c levels and casual postprandial plasma glucose (CPPG), and coefficient of variation and average of extraglycemic parameters in diabetic cohorts were determined. Results: The glycemic variability and variability of extraglycemic factors in SGLT2i cohort were smaller than those in non-SGLT2i cohort. However, only smaller coefficient of variation of HbA1c improved some neuropathy outcome measures, and ameliorated eGFR decline. SGLT2i improved the Z-score of neurophysiological tests. Favorable changes in averaged blood pressure, HDL-cholesterol and uric acid by SGLT2i led to neurological and renal protection, but did not halt the progress of the retinopathy. Conclusion: Over 3 years period, SGLT2i significantly improved some neuropathy outcome measures, mean Z-score of 8 neurophysiological tests, and attenuated nephropathy in modestly controlled type 2 diabetes by reducing glycemic variability and mean nonglycemic factors of diabetic microvascular complication.